Monoclonal antibody development and antigenic epitope identification of chicken pro-IL-1β - Mengmeng Xu; Mengmeng Huang; Guodong WANG; Jingzhe HAN; Xinxin NIU; Jinze HAN; Hangbo YU; Yulong ZHANG; Runhang LIU; Ziwen WU; Hongyu Cui; Yanping Zhang; et al. (Poultry Science)
Pro-IL-1β is an important inflammatory factor and is also a biomarker for detecting early pro-inflammatory immune responses. However, commercially available antibodies against chicken inflammatory factors are lacking, which prohibits an in-depth exploration of the mechanism of chicken inflammation. This study cloned and expressed chicken pro-IL-1β, and developed a hybridoma cell line 1E12 capable of stably secreting chicken pro-IL-1β monoclonal antibody (mAb). The secreted mAb 1E12 can recognize exogenous or endogenous chicken pro-IL-1β by Western blot and IFA techniques, and for the first time, a novel antigen epitope 13SSLSEETFY21 of chicken pro-IL-1β recognized by this mAb was identified. This study not only provides an important tool for the detection and research of chicken pro-IL-1β, but also has significant implications for understanding the antigenic structure and biochemical characteristics of chicken pro-IL-1β.